Error Control Coding (S. Lin and D. J. Costello; 2004) [book review] - Blake, Ian F. (IEEE transactions on information theory, 2005)
This book provides an encyclopedic treatment of the evolution of error coding over the past several decades. It focuses in a consistent manner on those aspects of the subject that pertain to real applications and especially on the construction and application of modern error control techniques. It deals mainly with binary codes and finite fields. The book also gives a very large number of detailed examples that examine and extend the theoretical treatment. This volume, in addition to updating and considerably expanding the chapters of the previous edition, has added seven new chapters. The added chapters cover such topics as trellis and block coding techniques, three chapters on soft decoding methods for block codes and substantial chapters on turbo and low-density parity-check.